The consequences of ultra-processed foods on brain development during prenatal, adolescent and adult stages - Mottis, Gaia; Kandasamey, Pratheba; Peleg-Raibstein, Daria (Frontiers in Public Health, 2025)
Ultra-processed foods (UPFs) are highly refined formulations of non-nutritive compounds containing elevated amounts of sugar, fat, sodium, food additives, and dietary emulsifiers. Consumption of UPF is robustly linked to a range of non-communicable diseases, including obesity, type 2 diabetes, cardiovascular disease, and mental disorders in adults. While substantial research highlights the negative health impacts of UPFs in adulthood, their effects on brain development during critical periods of biological vulnerability, pregnancy, childhood, and adolescence, remain underexplored. During pregnancy, significant metabolic and physiological adaptations occur to support fetal growth, making maternal diet quality essential for optimal perinatal outcomes. Poor maternal nutrition, including high UPF consumption, has been associated with an increased risk of hypertensive disorders, gestational diabetes, and adverse birth weights, potentially predisposing offspring to metabolic health disorders later in life. Similarly, in early childhood, inadequate nutrition is a key risk factor for developmental impairments, influencing cognitive function and long-term health outcomes. Adolescence, another critical stage of brain maturation, is particularly susceptible to the effects of micronutrient deficiencies, often exacerbated by diets high in UPFs, which can impair neurodevelopment and cognitive performance. As UPFs continue to dominate modern diets, accounting for over 50% of total energy intake in some developed nations, understanding their long-term impact on brain development is crucial. Early-life exposure to UPFs may contribute to lasting cognitive deficits and increased susceptibility to mental health disorders, emphasizing the urgent need for targeted dietary interventions and public health strategies aimed at pregnant women, children, and adolescents.